Fat Grafting Volume Restoration to the Brow and Temporal Regions - Tzikas, Thomas L. (Facial Plastic Surgery, 2018)
Primary manifestations of facial aging are the reduction in subcutaneous tissue volume, especially the atrophy of fat as well as bone volume depletion which directly contribute to loss of support and laxity of the skin. Depressions and hollows develop with a visible disruption of the cosmetic facial aesthetic units resulting in harsh shadows. This is especially evident in the eyebrow and temporal regions which accentuate the appearance of brow ptosis and a hollow, almost cadaveric look to the temple. Restoration of volume to these areas has been shown to rejuvenate the upper face creating a softer, fuller, and more youthful appearance. Fat grafting by itself or in combination with upper facial surgical procedures plays a major role in the restoration of youthful facial qualities in this region.
Keywords: fat grafting; fat transfer; autologous fat grafting; temporal hollow; eyebrows; upper facial rejuvenation